Arkeologi Kawasan Dan Kawasan Arkeologis: Asas Keseimbangan Dalam Pemanfataan - Timbul Haryono (Balai Arkeologi Yogyakarta, 1995)
Although archaeological studies study the human past based on the objects left behind, in its implementation, archaeological studies are not sufficient to only orientate toward artifacts. Human artifacts from the past cannot be separated from the spatial context, both on a micro and macro scale.